(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The low ICT literacy level of NCE graduates in Nigeria was attributed to the level of ICT skills possessed by lecturers in colleges of education. This study was aimed at investigating the ICT skills possessed by academic staff of colleges of education in south western Nigeria. Three research questions guided the conduct of the study. Survey design was adopted for the study. The population of the study consisted of 379 programme administrators. 229 programme administrators constituted the sample used for the study. A questionnaire titled ’Teacher ICT Skills Assessment Questionnaire (TICTSAQ)’ was developed by the researcher on a 4-point response scale and used for the collection of data. The instrument was validated by four experts. The reliability coefficient of the instrument was 0.76 using the Cronbach Alpha. The analysis of data was done using arithmetic mean. The results revealed that lecturers did not possess all ICT skills assessed in the study. It was recommended among others that teacher education curricula should be reviewed by the government to include ICT skills not possessed by lecturers.